Appraisal on Social Perception Pertaining to Communication and Psychology - Norashikin Abdul Hamid; Raha Abdul Rahman; Mohd Idrus Mohd Masirin; M Ikhsan Setiawan; Sri Wiwoho Mudjanarko; Fauzilah Salleh (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: This paper discusses what is social perception, social perception aspects of non-verbal communication, attribution, and impression formation, and also some suggestions on how social perception affected cultures. Design/methodology/approach: Describe your method here. This research is a literature study research. The first step was to collect literature relevant to the topic. The second step was data reduction, which is reduced data and chosen the main data. The third step was presented the data and the last step was concluded. Findings: Impaired social perception can have serious social consequences. For example, an adolescent boy might misread a girl’s sympathetic smile as a romantic invitation, and proceed to respond in a sexually offensive manner or a child might misread a peer’s teasing gesture as a threat and react aggressively. In these cases, the socially unsuccessful responses were not a result of inadequate social skills. Rather, they resulted from social “misreading”, that is, impaired social perception. Not surprisingly, the more we get to know someone, the more accurate we are at describing their traits and motives. Even when judging people we know well, however, the shortcuts we use sometimes lead to mistaken impressions. As these examples suggest, effective social perception contributes in important ways to social success, peer acceptance, and friendship. Research limitations/implications: This research is a literature review research. Further empirical research is needed. Practical implications: Results of this research can be used as references in appraisal on social perception about communication and psychology. Originality/value: This paper is original. Paper type: A literature review